Порівняльний аналіз методів, застосовуваних для ранньої діагностики цукрового діабету - Лихоносова, А. П.; Лихоносов, М. П. (Clinical Endocrinology and Endocrine Surgery, 2012)
Lecture shows comparative study of various analytical methods of diagnostics and treatment control of diabetes mellitus and metabolic syndrome such as methods of evaluation of glycemia, glucose in urine, glicated haemoglobin and microalbuminuria.